The impact of an alkasite restorative material on the pH of Streptococcus mutans biofilm and dentin remineralization: an in vitro study - Pawinee Wiriyasatiankun; Rangsima Sakoolnamarka; Panida Thanyasrisung (BMC, 2022)
Abstract Background It has been claimed that an alkasite restorative material can neutralize acids produced by cariogenic bacteria from released hydrogen ions and enable to remineralization via calcium and fluoride ions. However, there is no evidence to support this assertion. Therefore, the aims of this study were to investigate the effect of the alkasite restorative material on the pH of Streptococcus mutans biofilm and dentin hardness. Methods Streptococcus mutans biofilms were formed on Filtek™ Z350 (FZ, a resin composite) and Cention® N (CN, the alkasite restorative material) and their pH determined after 24 h. Hydroxide, fluoride, and calcium-ions released from the materials were determined at 6 h, 1, 3, 7, 14, and 28 days. Dentin specimens were prepared from 14 human molars and divided into four quadrants. Quadrant 1 was a sound dentin control, quadrants 2-4 were chemically demineralized, and a cylinder of FZ and CN placed on the surfaces of quadrants 2 and 4, respectively. The microhardness of quadrants 1 and 3 were measured at depths of 20, 40, and 60 µm from the occlusal surface, and similarly of quadrants 2 and 4, after 30 days. Independent t-test, Mann-Whitney-U, and repeated-measure-ANOVA were used for data analysis. Results The pH of biofilm on CN (4.45) was significantly higher (p < 0.05) than that on FZ (4.06). The quantity of all ions released from CN was significantly higher than from FZ. The hardness of demineralized dentin under CN was significantly higher than that of demineralized dentin at all depths, and higher than that of demineralized dentin under FZ at 20 and 40 µm. Conclusions CN released hydroxide, fluoride, and calcium ions, which was associated with raising the biofilm pH and the hardness of demineralized dentin. All results indicated that CN had the potential to reduce the incidence of secondary caries.